How to live in the city - Macdonald, Hugo, ....- (London : Macmillan, 2016)
Building a relationship with a city is a lot like building a relationship with another person - just as cities can be intoxicating, generous and inspiring, so they can also be dangerous, fickle and impenetrable. How to Live in the City is a book for navigating and nurturing this important relationship. Hugo Macdonald believes you need to feel a city to understand it. He won't tell you how wide the perfect pavement should be but he will show you how to walk down a pavement with eyes wide open. This is a book to help you feel human in an inhuman environment.
Keywords: Samenleving ; stad